ANALISIS PERILAKU NARSISTIK REMAJA BUDDHIS PENGGUNA APLIKASI TIKTOK DI DESA MOJOREJO, KECAMATAN JUNREJO - Kurniati Kurniati (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2021)
Adolescence is a period of transition from childhood to adulthood, has a sense of curiosity and a search for identity by displaying narcissistic behavior to be recognized in society. Narcissism is displayed through social media, one of which is the TikTok application. The purpose of this study is to find out the causes and effects of the use and impact of the TikTok application and the relationship between the use of the TikTok application and the narcissistic behavior of Buddhist adolescents. The method in this study is descriptive qualitative and primary data sources obtained through observation, interviews and documentation. The results of this study indicate that the use of the TikTok application by Buddhist youth in Mojorejo Village is caused; entertainment, seeking information and keeping up with the times. The positive impact of the TikTok application is being confident, active, increasing knowledge. In addition, the negative impacts that arise are difficulty managing time, the emergence of a sense of laziness, and difficulty controlling emotions. Narcissistic behavior is shown by Buddhist adolescents from the desire to have many followers, and aggression as a response when getting reprimanded.